Limited enzymatic hydrolysis reshapes whey protein antigenicity, taste profile, and techno-functional properties - Meng-Qi Liu; Wen-Qi Liang; Di Su; Ying-Hua Zhang; Zhi-Shen Mu (Food Chemistry, 2026)

Protein glutaminase–mediated deamidation improves the hydration properties of spray-dried micellar casein powders by coupling hierarchical porosity with surface charge and hydrophobicity modulation - Yi-Fang Gao; Stella Zhu; Di Su; Ying-Hua Zhang; Zhi-Shen Mu (Food Chemistry, 2026)

Hydrodynamic characteristics of a partitioned recirculating aquaculture pond - Yuxin Liu; Jun Zhang; Shouqi Cao; Di Mu; Xingguo Liu; Bin Wang; Qian Yang; Yusheng Sun (Aquacultural Engineering, 2026)

Long-range transported dust enhances ice nucleating particle abundance in the North China Plain - Yue Sun; Yujiao Zhu; Hengde Liu; Lanxiadi Chen; Hongyong Li; Yujian Bi; Di Wu; Xiangkun Yin; Can Cui; Ping Liu; Yu Yang; Jisheng Zhang; et al. (Journal of Environmental Sciences, 2026)

CNTN6 Modulates Slit-Robo Signaling in Cortical GABAergic Interneuron Migration - Yiliang Xu; Tian Zhao; Dan Zhao; Wei Zhang; Di Mu; Ailing Gui; Junzhi Guo; Kazutada Watanabe; Zhi-Cheng Xiao; Haihong Ye (Neuroscience Bulletin, 2026)

Study on failure mechanism and prediction model of horizontal tanks under fragment impact with varying filling conditions - Zilong Deng; Mingshu Bi; Yubin Mu; Di Yu; Qiangqiang Hao; Jingjie Ren (Process Safety and Environmental Protection, 2026)

Imidazole-based dual-function molecular structure for a cross-cycle-resistant, long-cycle, membrane-free, anode-free zinc-based battery - Zhenhe Chang; Rui Mu; Wei Zhang; Chaoyue Zhang; Ziang Yao; Haotong Wang; Baohui Wang; Hongjun Wu; Di Gu (Chemical Engineering Journal, 2026)

Experimental investigation of contaminant dispersion in vertical drainage pipes induced by toilet flushing - Di Mu; Min Chang; Lu Feng; Ruibin Li; Yan Wu; Naiping Gao (Building and Environment, 2026)

Lignin-based carbon quantum dots with adjustable singlet oxygen production for antibacterial application - Jiangze Wang; Li Li; Jianglei Sun; Yuxi Shi; Kaixuan Duan; Di An; Ya Zhou; Tong Mu; Die Hu; Tingxin Qian; Chao Liu; Chao Deng; et al. (Chemical Engineering Journal, 2026)

N-doped ordered mesoporous carbon embedded with Ni-N₃-Pyr sites achieve nearly 100% selectivity for CO₂RR to CO - Di Jin; Yunpeng Zou; Yang Zhao; Shuai Chen; Shiwei Luo; Taotao Chen; Jinchuan Zhang; Jialin Chen; Jijie Li; Yuewen Mu; Wen-Yan Zan; Fengwei Zhang (Journal of Environmental Chemical Engineering, 2026)

Numerical investigation of toilet flushing and exhaust fan operation on aerosol transmission dynamics in building drainage system - Di Mu; Min Chang; Lu Feng; Ruibin Li; Yan Wu; Naiping Gao (Building and Environment, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Experimental study on explosive boiling of superheated liquid caused by vessel crack propagation - Di Yu; Mingshu Bi; Qiangqiang Hao; Zilong Deng; Yubin Mu; Jinghao Zhang; Jianlei Zhang; Jingjie Ren (Process Safety and Environmental Protection, 2026)

The reactive oxygen species-induced small RNA CsrO promotes the survival of Cronobacter sakazakii in macrophages and systemic infection within the host - Xiaoya Li; Di Huang; Ruiying Liu; Qiyue Zhang; Xinyuan Yang; Jiake Wang; Min Wang; Qian Wang; Jianwei Mu; Xintong Chen; Miaomiao Liu; Sijia Liu; et al. (Food Research International, 2025)

Metagenomics and binning analysis unveiled the diversity and transfer patterns of antibiotic resistance genes in traditional pickled vegetables - Hui Wang; Xindi Mu; Tingting Su; Xiyuan Yang; Lei Xu; Di Yao; Liangyu Li (Food Bioscience, 2025)

Emission fluxes of nitrous acid (HONO) from livestock and poultry wastes - Wenjin Zhang; Pengfei Liu; Min Song; Xuran Li; Xiaoxi Zhao; Yifei Song; Di Tian; Chenglong Zhang; Yuanyuan Zhang; Yangang Ren; Chengtang Liu; Junfeng Liu; et al. (Journal of Environmental Sciences, 2025)

Intestinal metabolomic profiling provides insights into the molecular mechanisms for hyperuricemia-induced intestinal barrier dysfunctions in a hyperuricemia mouse model - Hailong Li; Qingli Zhang; Tingting Tang; Lei Zhu; Qu Chen; Haili Zhang; Yan Zhang; Zichu Zhao; Di Xiao; Xinlei Sha; Jingrong Mu; Jingjing Kong (Food and Chemical Toxicology, 2025)

Tailoring key intermediates and interfacial water at Ag92Ru8 aerogel toward sustainable ammonia synthesis from nitrate - Junjie Chen; Xiaomei Xing; Sisi Wen; Mengyuan Li; Di Liu; Wenji Jiang; Xinyi Shao; Ruikai Qi; Yumei Yang; Ming Mu; Zheng-jie Chen; Bing Zhao; et al. (Chemical Engineering Journal, 2025)

Construction of a Machine Learning-Based Clopidogrel Resistance Risk Prediction Model - Ruo-Ying Wang; Shui-Di Yan; Jian-Qi Zeng; Tong Mu; Ya Yan; Yuan-Yi Zhao; Lin Xie; Li-Li Liu (Cardiovascular Toxicology, 2025)

Wind-tide modulated net ecosystem metabolism in a Changjiang River Estuary aquaculture zone during mid-autumn - Di Wu; Kui Wang; Guoquan Wang; Qinglin Mu; Wei Fan; Dawei Xu (Marine Environmental Research, 2025)

Correlations and analysis of heat transfer coefficient for seawater falling film evaporation on horizontal tube - Qiang Meng; Shengqiang Shen; Chao Li; Di Wang; Xingsen Mu (Desalination, 2025)

Comprehensive analysis of single tube falling film heat transfer performance considering dynamic growth of fouling - Boyu Wang; Yuzhe Niu; Di Wang; Xingsen Mu; Yali Guo; Shengqiang Shen (Desalination, 2025)

Characteristics of loess landslides under the effects of faults and rivers and their correlations with geological and surficial evolutionary processes - Qi-qi Liu; Wan-li Xie; Hui Yang; Ming Yan; Rong-sen Zhu; Ke Mu; Yi-lun Chang; Shengjie Di; Xiaoliang He; Xiaomin Liu; Ying Zhang (Bulletin of Engineering Geology and the Environment, 2025)

A recursive segmentation model for bok choy growth monitoring with Internet of Things (IoT) technology in controlled environment agriculture - Chenchen Kang; Xinyang Mu; Aline Novaski Seffrin; Francesco Di Gioia; Long He (Computers and Electronics in Agriculture, 2025)

A novel and flexible way to derive water quality criteria for copper - Yang Li; Di Mu; Hong-Qing Wu; Xian-Hua Liu; Jun Sun; Zhi-Yong Ji (Science of The Total Environment, 2025)

Multiple-reprocessable guaiacol-derived epoxy vitrimer with disulfide crosslinks and closed-loop recycling of carbon fiber-reinforced composites - Kai Dong; Di Zhao; Yang Pang; Binghui Liu; Qian Liu; Tong Mu; Chengji Zhao (Chemical Engineering Journal, 2025)

Water-in-water emulsions stabilized by konjac glucomannan/tragacanth gum hydrogels for riboflavin delivery - Nitong Bu; Huanglong Lin; Di Zhang; Xianrui Chen; Pingping Tan; Yuanbo Zhong; Liying Huang; Jie Pang; Lin Wang; Ruojun Mu (Journal of Food Engineering, 2025)

Annual emissions of N2O, NO, HONO, and NH3 from maize-wheat fields in the North China Plain - Yifei Song; Yuanyuan Zhang; Minhang Tan; Yining Hu; Pengfei Liu; Di Tian; Yujing Mu (Science of The Total Environment, 2024)

Derivation of marine water quality criteria for copper based on artificial neural network model - Yang Li; Di Mu; Hong-Qing Wu; Xian-Hua Liu; Jun Sun; Zhi-Yong Ji (Environmental Pollution, 2024)

Risk assessment of cough droplets in both static and dynamic indoor environments with different ventilation strategies - Kaijun Li; Ruibin Li; Lingjun Xiao; Lu Feng; Di Mu; Xing Shi; Naiping Gao (Building and Environment, 2024)

Orthogonal photochemistry toward spatial reprogramming of 3D-printed liquid crystal elastomers - Hong Wan; Guancong Chen; Xiaorui Zhou; Hongfeng Mu; Chen Yang; Di Chen; Chujun Ni; Zizheng Fang; Qian Zhao; Tao Xie; Ning Zheng (Chemical Engineering Journal, 2024)

Experimental and numerical investigations of extreme wave impacting on a suspended structure - Di Mu; Dezhi Ning; Lifen Chen (Coastal Engineering, 2024)

Vertical transmission of aerosols between building flats through drainage system: A review - Min Chang; Di Mu; Yi Zhao; Lingjun Xiao; Yan Wu; Naiping Gao (Building and Environment, 2024)

SIRT1-Mediated HMGB1 Deacetylation Suppresses Neutrophil Extracellular Traps Related to Blood–Brain Barrier Impairment After Cerebral Venous Thrombosis - Shuwen Mu; Ziqi Li; Long Lin; Di Wang; Fei Yang; Li Chen; Liang Xian; Kunzhe Lin; Yinghong Lin; Dan Ye; Yang Yang; Liangfeng Wei; et al. (Molecular Neurobiology, 2024)

Spatial correlations in time and frequency domains between chlorophyll-a concentration and environmental factors in the Bohai Sea - Wan Xu; Di Mu; Zhenteng Yang; Dekui Yuan (Journal of Oceanology and Limnology, 2024)

Biocatalytic Au10 clusters for sepsis management via modulation of systemic inflammation - Qi Xin; Sufei Zhou; Lijie Zhang; Si Sun; Di Liu; Hao Wang; Xiaoyu Mu; Xiaoxing Fang; Qi Chen; Huanhuan Qiao; Xiao-Dong Zhang; Ruiping Zhang (Chemical Engineering Journal, 2024)

Effect of Maillard reaction based on catechol polymerization on the conversion of food waste to humus - Daichen Mu; Chao Wang; Xinyu Geng; Yue Zhao; Taha Ahmed Mohamed; Di Wu; Zimin Wei (Chemosphere, 2024)

Characterizing NOx emissions from diesel trucks with tampered aftertreatment systems and its implications for identifying high emitters - Miao Tian; Liqiang He; Di Peng; Mingliang Fu; Shuai Ma; Jinsong Mu; Quanshun Yu; Jia Wang; Hang Yin; Junfang Wang (Science of The Total Environment, 2024)

Advances and perspectives on the life-cycle impact assessment of personal protective equipment in the post-COVID-19 pandemic - Fangang Zeng; Di Liu; Can Xiao; Kuntai Li; Xuelin Qian; Yingru He; John P. Giesy; Yunsong Mu; Mengxiao Wang (Journal of Cleaner Production, 2024)

Efficient degradation of cellulosic ethanol wastewater by perovskite activation of Sr element A-site doped lanthanide copper chalcogenide materials - Likun Huang; Huixian Wang; Guangzhi Wang; Deying Mu; Yue Hou; Xinyi Di; Simin Zhou; Dongdong Wang; Dandan Wang (Environmental Science and Pollution Research, 2023)

Self-healing polyurethane coatings based on dynamic chemical bond synergy under conditions of photothermal response - Kang Chen; Haoxin Zhu; Zhiyi Zhang; Yingqing Shao; Qianhui Yu; Xinlei Cao; Siyan Pan; Xin Mu; Zhenhua Gao; Di Wang; Shuangying Wei; Shuaiyuan Han (Chemical Engineering Journal, 2023)

Derivation of copper water quality criteria in Bohai Bay for the protection of local aquatic life and the ecological risk assessment - Yang Li; Di Mu; Hong-Qing Wu; Hai-Jiao Liu; Yong-Hui Wang; Guo-Chen Ma; Xue-Min Duan; Jian-Jun Zhou; Chun-Ming Zhang; Xing-Hua Lu; Xian-Hua Liu; Jun Sun; et al. (Marine Pollution Bulletin, 2023)

Modeling Impact Load on a Vertical Cylinder in Dam-Break Flows - Di Mu; Lifen Chen; Dezhi Ning (Journal of Marine Science and Engineering, 2023)
A three-dimensional dam-break flow interacting with a vertical circular and square cylinder is studied in this paper using computational fluid dynamics simulations based on OpenFOAM. This resembles closely a tsunami wave and greenwater flow acting on coastal or on-deck structures, which are of relevance and importance to coastal protections and offshore operations, respectively. The numerical model is verified by comparing with published experimental measurements and is extended to investigate the effects of the structural geometry and the impacting angle β (i.e., the angle between the water front and cylinders) on the total impact load and the surrounding flow field. It is found that the impact event experiences two distinct stages characterized by a constant flow velocity and a negative flow acceleration, respectively. In addition, the total force on a square cylinder is nearly twice that of a circular cylinder although the impacting area is the same. The longitudinal and transverse forces are found to decrease and increase with the impacting angle, respectively. A close interrogation of the surrounding flow field via flow visualization suggests that the way the flow deflected from the cylinder surfaces plays an important role in determining the pressure field and thus the total force behaviors.

Longitudinal expression profiles of flavonoid synthesis-related genes and their correlations with contents of flavonoids including anthocyanins in purplish-green aerial stems of Panax notoginseng - Hongling Zhang; Guiqiong Li; Min Jiang; Changling Zhao; Pengyu Zhao; Chen Wang; Guosong Wen; Feng Zhou; Wenhua Dongchen; Shaozhong Xu; Ting Mu; Fanlai Meng; et al. (Acta Physiologiae Plantarum, 2023)

Seismic behavior of precast segmental column bridges under near-fault forward-directivity ground motions - Xin Lifeng; Li Xiaozhen; Fu Peiyao; Mu Di (Earthquake Engineering and Engineering Vibration, 2022)

Simultaneous detection of ten kinds of insecticide residues in honey and pollen using UPLC-MS/MS with graphene and carbon nanotubes as adsorption and purification materials - Xiuyu Pang; Chenyu Li; Chuanjiang Zang; Lei Guan; Peng Zhang; Chunxiang Di; Nan Zou; Beixing Li; Wei Mu; Jin Lin (Environmental Science and Pollution Research, 2022)

Molecular Evolution of Tooth-Related Genes Provides New Insights into Dietary Adaptations of Mammals - Yuan Mu; Ran Tian; Linlin Xiao; Di Sun; Zepeng Zhang; Shixia Xu; Guang Yang (Journal of Molecular Evolution, 2021)
Mammals have evolved different tooth phenotypes that are hypothesized to be associated with feeding habits. However, the genetic basis for the linkage has not been well explored. In this study, we investigated 13 tooth-related genes, including seven enamel-related genes ( AMELX , AMBN , ENAM , AMTN , ODAM , KLK4 and MMP20 ) and six dentin-related genes ( DSPP , COL1A1 , DMP1 , IBSP , MEPE and SPP1 ), from 63 mammals to determine their evolutionary history. Our results showed that different evolutionary histories have evolved among divergent feeding habits in mammals. There was stronger positive selection for eight genes ( ENAM , AMTN , ODAM , KLK4 , DSPP , DMP1 , COL1A1 , MEPE ) in herbivore lineages. In addition, AMELX , AMBN , ENAM , AMTN , MMP20 and COL1A1 underwent accelerated evolution in herbivores. While relatively strong positive selection was detected in IBSP , SPP1 , and DSPP , accelerated evolution was only detected for MEPE and SPP1 genes among the carnivorous lineages. We found positive selection on AMBN and ENAM genes for omnivorous primates in the catarrhini clade. Interestingly, a significantly positive association between the evolutionary rate of ENAM , ODAM , KLK4 , MMP20 and the average enamel thickness was found in primates. Additionally, we found molecular convergence in some amino acid sites of tooth-related genes among the lineages whose feeding habit are similar. The positive selection of related genes might promote the formation and bio-mineralization of tooth enamel and dentin, which would make the tooth structure stronger. Our results revealed that mammalian tooth-related genes have experienced variable evolutionary histories, which provide some new insights into the molecular basis of dietary adaptation in mammals.

SARS-CoV-2-encoded nucleocapsid protein acts as a viral suppressor of RNA interference in cells - Jingfang Mu; Jiuyue Xu; Leike Zhang; Ting Shu; Di Wu; Muhan Huang; Yujie Ren; Xufang Li; Qing Geng; Yi Xu; Yang Qiu; Xi Zhou (Science China Life Sciences, 2020)

Use of near-isogenic lines to precisely map and validate a major QTL for grain weight on chromosome 4AL in bread wheat (Triticum aestivum L.) - Panfeng Guan; Na Di; Qing Mu; Xueyi Shen; Yongfa Wang; Xiaobo Wang; Kuohai Yu; Wanjun Song; Yongming Chen; Mingming Xin; Zhaorong Hu; Weilong Guo; et al. (Theoretical and Applied Genetics, 2019)

Remote sensing monitoring of the suspended particle size in Hongze Lake based on GF-1 data - Shaohua Lei; Di Wu; Yunmei Li; Qiao Wang; Changchun Huang; Ge Liu; Zhubin Zheng; Chenggong Du; Meng Mu; Jie Xu; Heng Lv (International Journal of Remote Sensing, 2019)

Effects of dietary Allium mongolicum Regel polysaccharide on growth, lipopolysaccharide-induced antioxidant responses and immune responses in Channa argus - Mu-Yang Li; Xin-Ming Zhu; Xiao-Tian Niu; Xiu-Mei Chen; Jia-Xin Tian; Yi-Di Kong; Dong-Ming Zhang; Lei Zhao; Gui-Qin Wang (Molecular Biology Reports, 2019)

The features as a county of Chu State: chemical and metallurgical characteristics of the bronze artifacts from the Bayilu site - Di Mu; Wugan Luo; Guoding Song; Baotong Qiao; Fengjian Wang (Archaeological and Anthropological Sciences, 2019)

The bronze artifacts from the Yejiashan site and the political presence of the Zhou dynasty in the middle Yangtze Plain: an application of lead isotope analysis - Di Mu; Wugan Luo; Fengchun Huang; Guoding Song (Archaeological and Anthropological Sciences, 2018)

Analysis of the function of KIF3A and KIF3B in the spermatogenesis in Boleophthalmus pectinirostris - Yong-Qiang Zhao; Dan-Li Mu; Di Wang; Ying-Li Han; Cong-Cong Hou; Jun-Quan Zhu (Fish Physiology and Biochemistry, 2018)

Sourcing copper ores for production of bronzes excavated at Shuangyantang, a Western Zhou (1046–771 bc) site in Chongqing (Southwest China): evidence from lead isotope analysis - Xiaopan Fan; Di Mu; Jun Yi; Hongmin Wang; Wugan Luo (Archaeological and Anthropological Sciences, 2016)

A sensitive and accurate quantification method for the detection of hepatitis B virus covalently closed circular DNA by the application of a droplet digital polymerase chain reaction amplification system - Di Mu; Liang Yan; Hui Tang; Yong Liao (Biotechnology Letters, 2015)

Enhanced lipid accumulation and biodiesel production by oleaginous Chlorella protothecoides under a structured heterotrophic-iron (II) induction strategy - Yuqin Li; Jinxiu Mu; Di Chen; Hua Xu; Fangxin Han (World Journal of Microbiology and Biotechnology, 2015)

Proteomics analysis for enhanced lipid accumulation in oleaginous Chlorella vulgaris under a heterotrophic-Na+ induction two-step regime - Yuqin Li; Jinxiu Mu; Di Chen; Hua Xu; Fangxin Han; Bo Feng; Hongyan Zeng (Biotechnology Letters, 2015)

Catalpol Inhibited the Proliferation of T24 Human Bladder Cancer Cells by Inducing Apoptosis Through the Blockade of Akt-Mediated Anti-apoptotic Signaling - Di Jin; Ming Cao; Xin Mu; Guoliang Yang; Wei Xue; Yiran Huang; Haige Chen (Cell Biochemistry and Biophysics, 2015)

Enhanced organic phosphorus detection in sediments by foam separation and 31P-NMR - Yuxin Shi; Tengfei Pan; Di Mu; Hongqin Wu; Qingqiang Meng; Shuting Qi (Environmental Chemistry Letters, 2014)

THE IMPACTS OF CLIMATE CHANGE ON WATER STRESS SITUATIONS IN THE YELLOW RIVER BASIN, CHINA - Jianxin Mu; Qunchang Liu; Hamza Farooq Gabriel; Di Xu; Jingdong Xu; Caili Wu; Hejing Ren (Irrigation and Drainage, 2013)
This paper used a back‐propagation (BP) neural network to conduct statistical downscaling based on the data (two factors: precipitation and temperature) downscaled by the National Climate Centre of China from over 20 global circulation models (GCMs) and input these downscaled data into the Basin‐wide Holistic Integrated Water Assessment (BHIWA) model to analyse irrigation water demand as well as water stress situations in both water quantity and quality in the Yellow River Basin, China. The results of the changes in climate in scenarios A1B, A2 and B1/B2 showed that irrigation water demand will increase and the water situation will become more stressed in 2030 and 2050, though there is still some increase in precipitation in most of the sub‐basins in these scenarios. Meanwhile, with the same variation range of precipitation and ET 0 , ET 0 will have a bigger impact on irrigation water demand and water stress situations than precipitation, This implies that ET 0 is a more dominant factor influencing water demand and water stress situations than other meteorological parameters such as precipitation. In addition to this, groundwater quality is more vulnerable to climate change than surface water quality and better water management will result in a decrease in irrigation water demand. Copyright © 2013 John Wiley & Sons, Ltd.

A STOCHASTIC APPROACH TO ANALYSE WATER MANAGEMENT SCENARIOS AT THE RIVER BASIN LEVEL - Jianxin Mu; Shahbaz Khan; Qunchang Liu; Di Xu; Jingdong Xu; Wenhao Wang (Irrigation and Drainage, 2013)
Quantitative analysis techniques have gained a great deal of popularity with decision‐makers and analysts in recent years, and this is also the case in the hydrology sector. In this paper, the Basin‐wide Holistic Integrated Water Assessment (BHIWA) model developed by the International Commission on Irrigation and Drainage (ICID) was updated by the author to simulate the water balance of the Yellow River Basin in China, as well as to analyse the impacts of land and water use on return flows of this basin under past (1980), present (2000), and future (2030 and 2050) conditions. Stochastic analysis was then carried out using the Monte Carlo simulation method, by randomly selecting sets of values for the probability distributions in the cell values and formulas to quantify the risks in terms of water quantity and quality resulting from return flow. The model amply demonstrates the serious water shortage situation in the future. Developing the strategy of water‐saving measures would greatly enhance the efficiency of irrigation water use, and decrease water withdrawal for irrigation. In addition to this, a possible opportunity to transfer water from the Yangtze River to the Yellow River also came to light. Copyright © 2013 John Wiley & Sons, Ltd.

Synthesis, physico-chemical properties, and antimicrobial evaluation of a new series of iron(III) hexadentate chelators - Yuan-Yuan Xie; Mu-Song Liu; Pan-Pan Hu; Xiao-Le Kong; Di-Hong Qiu; Ji-Lin Xu; Robert C. Hider; Tao Zhou (Medicinal Chemistry Research, 2013)

Complete nucleotide sequence of a Chinese isolate of Grapevine leafroll-associated virus 3 reveals a 5′ UTR of 802 nucleotides - Fei Fei; Mu-Di Lyu; Jie Li; Zai-Feng Fan; Yu-Qin Cheng (Virus Genes, 2013)

NUMERICAL SIMULATIONS AND VALIDATION OF WATER FLOW AND HEAT TRANSPORT IN A SUBSURFACE DRIP IRRIGATION SYSTEM USING HYDRUS‐2D - Jiandong Wang; Shihong Gong; Di Xu; Sui Juan; Jianxin Mu (Irrigation and Drainage, 2013)
Subsurface drip irrigation (SDI) systems are often recommended to overcome water scarcity in arid and semi‐arid regions. To properly manage SDI systems, precise prediction of distribution and transport of soil water content and temperature (important soil physical factors for plant growth) around the emitters must be known. In this paper, the computer software package HYDRUS‐2D was used to evaluate the distribution and transport of soil water content and temperature around an emitter in a silt loam soil. The model was validated by comparison with measured data from field experiments involving SDI with emitters installed at 25‐cm soil depths. Model performance in simulating soil moisture and temperature was evaluated by comparing measured and predicted values using three parameters: model efficiency (ME), root mean square deviation (RMSE) and mean bias error (MBE). Values of ME, RMSE and MBE between measured and simulated soil moisture ranged from 0.71 to 0.84, 0.013 to 0.019 and 0.004 to 0.007 and between measured and simulated soil temperature ranged from 0.81 to 0.86, 0.97 to 1.33 and 0.13 to 0.28, respectively. Based on these values, it can be concluded that there was good correspondence between simulations and observations and the HYDRUS‐2D can be commendably used to describe soil water and heat transport properties involving SDI and also for investigating and designing drip irrigation management practices. Copyright © 2013 John Wiley & Sons, Ltd.

Effects of 1,1,1-trichloroethane on enzymatic activity and bacterial community in anaerobic microcosm form sequencing batch reactors - Hui Li; Wei Zhang; Lu Li; Yong-Di Liu; Kuang-Fei Lin; Shu-Guang Lu; Bo-Zhong Mu; Xiao-Ming Du; Qiang Lu; Qian Zhang; Ting-Ting Shen; Bing-Zhi Li; et al. (Ecotoxicology, 2012)

Optimisation of preparation conditions and properties of phytosterol liposome-encapsulating nattokinase - Xu-Yan Dong; Fan-Pi Kong; Gang-You Yuan; Fang Wei; Mu-Lan Jiang; Guang-Ming Li; Zhan Wang; Yuan-Di Zhao; Hong Chen (Natural Product Research, 2012)